2012
DOI: 10.1002/art.34385
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity of sensory and sympathetic nerve fibers in a mouse model of a painful arthritic joint

Abstract: Objective Many forms of arthritis are accompanied by significant chronic joint pain. Here we studied whether there is significant sprouting of sensory and sympathetic nerve fibers in the painful arthritic knee joint and whether nerve growth factor (NGF) drives this pathological reorganization. Methods A painful arthritic knee joint was produced by injection of complete Freund’s adjuvant (CFA) into the knee joint of young adult mice. CFA-injected mice were then treated systemically with vehicle or anti-NGF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
131
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 48 publications
12
131
0
Order By: Relevance
“…MI increases cardiac GAP43 expression in the infarcted area [48,49]. GAP43 is a marker of nerve sprouting, and tyrosine hydroxylase (TH) is a marker of sympathetic nerve fibers [50]. In the present study, the densities of the TH-and GAP43-positive fibers in the MI group were significantly increased when compared with the control and sham groups.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…MI increases cardiac GAP43 expression in the infarcted area [48,49]. GAP43 is a marker of nerve sprouting, and tyrosine hydroxylase (TH) is a marker of sympathetic nerve fibers [50]. In the present study, the densities of the TH-and GAP43-positive fibers in the MI group were significantly increased when compared with the control and sham groups.…”
Section: Discussionsupporting
confidence: 46%
“…The TH/GAP43 value in the MI rats treated with NONRATT021972 siRNA was significantly decreased compared to the MI group. The modulation of cardiac sympathetic signaling is a major therapeutic strategy to prevent and treat the symptoms of angina pectoris in 50-60 % patients with coronary heart disease [48][49][50][51][52]. The NONRATT021972 siRNA treatment might decrease the abnormal innervations of the cardiac sympathetic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast to the significant effects of ABT-102 (Table 3) and ABT-116 (data not shown), both of which fully block acid activation of TRPV1 and elicit hyperthermia in a mouse model of tumorinduced pain. A likely explanation for this result is that, mechanistically, osteoclast-induced acidosis plays a much more significant role in driving bone cancer pain (Mantyh, 2006) than OA pain (Ghilardi et al, 2012). These results are also consistent with clinical studies demonstrating that therapies that block osteoclast function, such as denosumab and bisphosphonates, show greater efficacy in relieving bone cancer pain (Rades et al, 2010) than OA pain (Dray and Read, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…Co-existence of GAP-43 with sensory and autonomic neuropeptides SP, CGRP and NPY further strengthens this notion. Interestingly, it has been reported that sensory and autonomic nerve fibers innervating aged knee joint maintain the capacity for nerve sprouting after inflammation or injury in mouse models [13] [20] [21]. The phenomenon of pathologic nerve regeneration in the human inflamed synovium as seen in the present study probably contributes to chronic joint pain and underlying changes in OA joints and may provide pharmacological insight and targets for better controlling pain in chronic musculoskeletal disorders.…”
Section: Discussionmentioning
confidence: 49%
“…Further, a link between autonomic neuropeptides NPY, VIP and TH with the degree of synovial inflammation in rheumatoid arthritis (RA) and OA has been reported [11] [12]. Sprouting of sensory and autonomic nerve fibers has been suggested to occur in painful arthritic joint in experimental arthritis [13].…”
Section: Introductionmentioning
confidence: 99%